Current Landscape of Methods to Evaluate Antimicrobial Activity of Natural Extracts - GONZALEZ PASTOR, REBECA EUGENIA; Saskya E. Carrera-Pacheco; ZUÑIGA MIRANDA, JOHANA JANINA; Cristina Rodríguez-Pólit; MAYORGA RAMOS, ARIANNA CAROLINA; GUAMAN BAUTISTA, LINDA PRISCILA; Carlos Barba-Ostria (MDPI AG, 2023)
Natural extracts have been and continue to be used to treat a wide range of medical conditions, from infectious diseases to cancer, based on their convenience and therapeutic potential. Natural products derived from microbes, plants, and animals offer a broad variety of molecules and chemical compounds. Natural products are not only one of the most important sources for innovative drug development for animal and human health, but they are also an inspiration for synthetic biology and chemistry scientists towards the discovery of new bioactive compounds and pharmaceuticals. This is particularly relevant in the current context, where antimicrobial resistance has risen as a global health problem. Thus, efforts are being directed toward studying natural compounds’ chemical composition and bioactive potential to generate drugs with better efficacy and lower toxicity than existing molecules. Currently, a wide range of methodologies are used to analyze the in vitro activity of natural extracts to determine their suitability as antimicrobial agents. Despite traditional technologies being the most employed, technological advances have contributed to the implementation of methods able to circumvent issues related to analysis capacity, time, sensitivity, and reproducibility. This review produces an updated analysis of the conventional and current methods to evaluate the antimicrobial activity of natural compounds.